Isolation of Bacteria from Remote High Altitude Andean Lakes Able to Grow in the Presence of Antibiotics - Dib, Julian Rafael (2009)
High altitude Andean lakes are placed in Puna desert over 4400 above sea level. Completely isolated, they are exposed to extreme environmental factors like high levels of salinity, UV radiation and heavy metals and low concentrations of phosphorus. Nevertheless, they are the habitat of enormous populations of three flamingo species that migrate among these Lakes. Previous reports have determined that bacteria isolated from these environments present high levels of resistance to antibiotics. The aim of this work was to determine the diversity of antibiotic resistant bacteria in water from Andean Lakes and their connection with flamingo enteric biota. Bacteria from water and birds faeces from high altitude Lakes: Laguna (L.) Aparejos, L. Negra, L. Vilama and L. Azul (all are located between 4,200 and 4,600 m altitude) were isolated by plating in five different Antibiotics (ampicillin, 100 microg ml(-1); chloramphenicol, 170 microg ml(-1); colistin , 20 microg ml(-1); erythromycin, 50 microg ml(-1) and tetracycline 50 microg ml(-1)). 56 bacteria were isolated and identified by 16 S rDNA sequencing. Antibiotic resistance profiles of isolated bacteria were determined for 22 different antibiotics. All identified bacteria were able to growth in multiple ATBs. Colistin, ceftazidime, ampicillin/sulbactam, cefotaxime, cefepime, cefalotin, ampicillin and erythromycin were the most distributed resistances among the 56 tested bacteria. The current results demonstrated that antibiotic resistance was abundant and diverse in high altitude Lakes. Also the present article indicates some useful patents regarding the isolation of bacteria able to grow in the present of antibiotics.